Enhancing human health and wellness through neighborhood development standards - Ruiz, Dominic (Kansas State University, 2015)
Formally debuted in 2014, WELL Building Standard v1.0 is the world’s first building standard focusing solely on health and wellness. The WELL Building Standard is a performance-based standard that is designed to improve human health outcomes by integrating medical research into the design and construction of buildings. However, given the relatively young age of the building standard, it does not yet address health at the community level. Focusing on the wellness concepts established in WELL Standard v1.0, this research project re-imagines the standard as a metric to measure the health and wellness of master-planned communities. Through an analysis of the WELL Building Standard and other health-related literature, this research project identifies design strategies, protocols, and policies that can be used to improve health outcomes at the community level.
Keywords: Urban Planning; Landscape architecture; Public Health; Nutrition; Kinesiology